Bekendheid, benutting en effectiviteit van professionaliseringsprikkels in het voortgezet onderwijs Rapportage Deelstudie 2 - Rekers-Mombarg, L.T.M (2022)
The research reported in this publication concerns the second sub-study of the project Administrative Power and the Effect of Professionalisation Incentives in Secondary Education. This sub-study focuses on the various incentives that the Ministry of Education, Culture and Science and organisations affiliated with OCW (for instance NRO, the Inspectorate and DUO, VO-raad, the Education Council and collective agreements) give to various actor groups in education. The aim is to maintain and improve the professional competencies of those actor groups. Incentives' is another word for professionalisation policy instruments (PBIs) and these can be categorised as PBIs arising from legislation or regulations, PBIs of a financial nature and PBIs intended to entice professionalisation activities through communication. For each PBI aimed at secondary education, the actor(s) targeted and the nature of the incentive were identified. For comparison with secondary education, this has also been done for PBIs in PO and MBO. To gain more insight into the familiarity, use, effectiveness and possible side effects, experts were interviewed and asked to fill in a digital questionnaire. Finally, a focus group meeting was held to discuss our findings in more detail on the basis of various propositions.